The role of microstructure in luminescent properties of Er-doped nanocrystalline Si thin films - Stepikhova, M. (2004)
In this contribution, we present a structural and photoluminescence (PL) analysis of Er-doped nanocrystalline silicon thin films produced by rf magnetron sputtering method. We show the strong influence of the presence of nanocrystalline fraction in films on their luminescence efficiency at 1.54 microm studied on a series of specially prepared samples with different crystallinity, i.e., percentage and sizes of Si nanocrystals. A strong increase, by about two orders of magnitude, of Er-related PL intensity in these samples with lowering of the Si nanocrystal sizes from 7.9 to about 1.5 nm is observed. The results are discussed in terms of the sensitization effect of Si nanocrystals on Er ions